Signature of dislocations and stacking faults of face‐centred cubic nanocrystals in coherent X‐ray diffraction patterns: a numerical study. (1st June 2015) - Dupraz, Maxime; Beutier, Guillaume; Rodney, David; Mordehai, Dan; Verdier, Marc
<x xml:space="preserve">Abstract</x> Crystal defects induce strong distortions in diffraction patterns. A single defect alone can yield strong and fine features that are observed in high‐resolution diffraction experiments such as coherent X‐ray diffraction. The case of face‐centred cubic nanocrystals is studied numerically and the signatures of typical defects close to Bragg positions are identified. Crystals of a few tens of nanometres are modelled with realistic atomic potentials and `relaxed' after introduction of well defined defects such as pure screw or edge dislocations, or Frank or prismatic loops. Diffraction patterns calculated in the kinematic approximation reveal various signatures of the defects depending on the Miller indices. They are strongly modified by the dissociation of the dislocations. Selection rules on the Miller indices are provided, to observe the maximum effect of given crystal defects in the initial and relaxed configurations. The effect of several physical and geometrical parameters such as stacking fault energy, crystal shape and defect position are discussed. The method is illustrated on a complex structure resulting from the simulated nanoindentation of a gold nanocrystal.